2019
DOI: 10.1029/2019jc015458
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and Phase of Diurnal SST Variations in the ACCESS‐S1 Model During the Suppressed Phase of the MJOs

Abstract: Diurnal variations of sea surface temperature (DV SST) can affect the heat and moisture fluxes at the air-sea interface during the suppressed phase of the MJO, thereby conditioning a favorable atmosphere environment for the subsequent MJO active phase. In order to better understand the causes and impacts of DV SST, and the modeling requirements for faithfully simulating these processes, we explore the DV SST and their influences on the air-sea fluxes during the suppressed phases of three MJO events using a glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 48 publications
2
8
0
Order By: Relevance
“…Furthermore, this framework can help reveal the sensitivity of the MJO, and convection in general, to diurnal SST fluctuations (e.g., Matthews et al, 2014) that are captured only with fine oceanic vertical resolution (~1 m in the upper ocean) and frequent (approximately hourly) ocean‐atmosphere coupling (e.g., J.‐Y. Hsu et al, 2019; Y. Li et al, 2013; Zhao & Nasuno, 2020). A collection of simulations, including fully coupled, atmosphere‐only, and 1‐D ocean coupled, can help identify the time scales of coupled feedbacks that most strongly enable or inhibit MJO fidelity and focus efforts to improve oceanic or atmospheric processes most relevant to those scales during model development cycles.…”
Section: Recent Progress In Understanding Modeling and Predicting Tmentioning
confidence: 99%
“…Furthermore, this framework can help reveal the sensitivity of the MJO, and convection in general, to diurnal SST fluctuations (e.g., Matthews et al, 2014) that are captured only with fine oceanic vertical resolution (~1 m in the upper ocean) and frequent (approximately hourly) ocean‐atmosphere coupling (e.g., J.‐Y. Hsu et al, 2019; Y. Li et al, 2013; Zhao & Nasuno, 2020). A collection of simulations, including fully coupled, atmosphere‐only, and 1‐D ocean coupled, can help identify the time scales of coupled feedbacks that most strongly enable or inhibit MJO fidelity and focus efforts to improve oceanic or atmospheric processes most relevant to those scales during model development cycles.…”
Section: Recent Progress In Understanding Modeling and Predicting Tmentioning
confidence: 99%
“…In 3D climate models, the individual component time-steps are larger than in this single AOSCM configuration and do not allow us to couple at such high frequency. Hsu et al (2019) show that with a 1-h coupling, they still have deficiencies in the phasing of the SST maximum but could not go far beyond in their AOGCM. Here the AOSCM configuration allows us to tackle this question with more details.…”
Section: Impact Of the Coupling Frequencymentioning
confidence: 98%
“…We may wonder if the simulated SST would better match the observed skin SST if the model resolution was increased near the surface. Besides, the role of vertical discretization has been raised in many studies (Bernie et al, 2005;Hsu et al, 2019;Ge et al, 2017) but these studies generally test resolution between 1 m and 10 m. Hsu et al (2019) assess the diurnal SST representation in the ACCESS-S1 model which also uses NEMO at a 1-m vertical resolution. They suggest that flaws in representing the diurnal warming may be due to insufficient vertical resolution or to deficiencies in vertical mixing in the NEMO model.…”
Section: In the Oceanmentioning
confidence: 99%
See 1 more Smart Citation
“…Gas exchange, such as carbon dioxide flux at the sea surface [12], is also affected by diurnal SST cycle, and it has also been suggested that including the diurnal cycle in the calculations of climate model could improve representations of climate variability [7]. Moreover, the diurnal air-sea interaction may play an essential role in the longer time scale of climate variabilities such as Madden-Julian oscillation (MJO), and El Niño and Southern oscillation (ENSO) [13][14][15][16][17]. For the shorter scale, δSST variation determines the formation of the short period and high SST phenomena, called hot event (HE) [18][19][20].…”
Section: Introductionmentioning
confidence: 99%